2019
DOI: 10.1371/journal.pone.0223589
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of the pharmacy-dispensed naloxone kit program in Ontario: A population-based study

Abstract: BackgroundNaloxone is a life-saving antidote for opioid overdoses. In June 2016, the Ontario government implemented the Ontario Naloxone Program for Pharmacies (ONPP) to enhance access to naloxone.ObjectiveWe examined the initial uptake of naloxone through the ONPP and characteristics of the individuals receiving and pharmacies dispensing naloxone kits.MethodsWe conducted a population-based study of all Ontario residents who received a naloxone kit between July 1, 2016 and March 31, 2018. This involved 1) a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…While all Canadian provinces and territories have publicly funded THN programs, research and evaluation of these programs in the scholarly literature is limited. A recent study from Ontario describes uptake of the province's pharmacy-dispensed naloxone kits in Ontario [27], and preliminary Subsample taken from distribution data, stratified by eligibility (self-reported risk), from January 2018 to December 2018. � Column percentages A Other genders reported include being a trans, and gender non-conforming B Take-home naloxone kit was replaced due to a previous kit being lost, stolen, confiscated or expired C Other site types include corrections, pharmacy, post-secondary, other (e.g housing sites, treatment centres, non-governmental and peer-led organization)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all Canadian provinces and territories have publicly funded THN programs, research and evaluation of these programs in the scholarly literature is limited. A recent study from Ontario describes uptake of the province's pharmacy-dispensed naloxone kits in Ontario [27], and preliminary Subsample taken from distribution data, stratified by eligibility (self-reported risk), from January 2018 to December 2018. � Column percentages A Other genders reported include being a trans, and gender non-conforming B Take-home naloxone kit was replaced due to a previous kit being lost, stolen, confiscated or expired C Other site types include corrections, pharmacy, post-secondary, other (e.g housing sites, treatment centres, non-governmental and peer-led organization)…”
Section: Discussionmentioning
confidence: 99%
“…While all Canadian provinces and territories have publicly funded THN programs, research and evaluation of these programs in the scholarly literature is limited. A recent study from Ontario describes uptake of the province’s pharmacy-dispensed naloxone kits in Ontario [ 27 ], and preliminary analyses of provincial THN programs in Ontario [ 28 ], Alberta [ 29 ], Manitoba [ 30 ], and British Columbia [ 15 ] have been published. Data from other jurisdictions are not directly comparable, due to differences in program structure, eligibility criteria, and scope [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In areas with poor access to naloxone, the perceived OIRD-to-death ratio is much higher, indicating an opportunity for growth and expansion of the free THN program. 12,20 The "standard" form of naloxone available in free THN kits is the injectable form, which is administered intramuscularly. Although injectable naloxone is available in all jurisdictions (except the Northwest Territories) throughout Canada at THN kit distribution sites, this route of administration may act as a barrier for use by the general public.…”
Section: Discussionmentioning
confidence: 99%
“…About one-quarter to one-third of opioid-related deaths in Ontario involve prescription opioids. 13,14 In addition, approximately 80% of people assessed at an emergency department for opioid toxicity had received an opioid prescription in the previous 3 years.…”
Section: Effectiveness Of Naloxone Distribution Programsmentioning
confidence: 99%
“…Despite the availability of these kits, naloxone dispensing by pharmacies is highly variable. A population-based study examining the uptake of THN in the Ontario Naloxone Program for Pharmacies in 2017 showed that only 55.6% of community pharmacies dispensed naloxone. 13 However, one-third (33.7%) of those THN kits were dispensed by the top 1% of naloxone-dispensing pharmacies. There was less uptake among prescription opioid recipients and those with past opioid exposure, regardless of their risk of OIRD. Over the 21-month study period, only 3918 of 55,000 (about 7%) of patients receiving high-dose opioids prescriptions ( > 90 mg morphine equivalents per day) were given THN in 2017. …”
Section: Effectiveness Of Naloxone Distribution Programsmentioning
confidence: 99%